In-vivo results for rheumatoid arthritis diagnosis with a 360 degrees pulse-echo imaging system - Koch, Andreas; Finzel, Stephanie; Kobler, Andreas; Schett, Georg; Lerch, Reinhard; Ermert, Helmut (IEEE SERVICE CENTER, 445 HOES LANE, PO BOX 1331, PISCATAWAY, NJ 08855-1331 USA, 2012)
Progress in medical ultrasound in recent years makes sonography a valuable method for early rheumatoid arthritis (RA) diagnosis today. However, detecting in ammatory processes in periarticular bones requires expert knowledge and training. 360 degrees compound imaging has already proven to increase ultrasound B-mode image quality significantly, e.g. in breast cancer imaging. Therefore an existing Ultrasound Computed Tomography (USCT) system has been modified for RA diagnosis, with respect to finger joint imaging. Well known concepts in USCT to reconstruct the speed of sound (SOS) distribution can not be applied, as the bone inhibits transmission measurements of fingers. Therefore, an image based local contrast quanti. cation method is proposed to estimate a mean SOS for the soft tissue surrounding the finger joint. Based on this estimation, ultrasound B-mode images can be corrected for refraction and TOF to yield high image quality in 360 degrees compound imaging. This method has been validated by measurements on tissue mimicking phantoms. Healthy volunteers and RA patients have been examined with the USCT system. In-vivo results show a great potential for 360 degrees compound imaging to visualize synovitis as well as bone erosion in RA of finger joints.
Keywords: rheumatoid arthritis; ultrasound computed tomography; full angle spatial compounding; speed of sound estimation; refraction correction; nger joints; in-vivo results